Lexical specification and insertion - Coopmans, Peter, 1958-; Everaert, Martin; Grimshaw, Jane B. (Jane Barbara), 1951- (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 2000)
The papers in this volume address the general question what type of lexical specifications we need in a generative grammar and by what principles this information is projected onto syntactic configurations, or to put it differently, how lexical insertion is executed. Many of the contributions focus on what the syntactic consequences are of choices that are made with respect to the lexical specifications of heads. The data in the volume are drawn from diverse languages, among which: Brazilian Portuguese, Bulgarian, Dutch, English, French, German, Icelandic, Italian, Mohawk, Norwegian, Polish, R.